2008
DOI: 10.1027/1015-5759.24.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Muñoz's Mood Screener in a Nonclinical Spanish Population

Abstract: Abstract. This study evaluates the utility of Muñoz's Mood Screener for detection of major depressive episodes in a nonclinical Spanish population. The Mood Screener was administered by face-to-face interview to 554 subjects (65.9% women; age 18-34 years) who were recruited by stratified random sampling from a population of 27,587 university students. Thereafter, two expert clinicians who were blind to the Mood Screener results independently administered a clinical interview (SCID-CV) as an aid in evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…We used the CES-D (31) to screen for current depressive symptoms and the Maternal Mood Screener (MMS) (32) to assess current and lifetime major depressive episode. The MMS is a self-report checklist to assess depressive episodes using DSM-IV criteria that has shown good concordance with diagnostic interviews (33,34). …”
Section: Methodsmentioning
confidence: 99%
“…We used the CES-D (31) to screen for current depressive symptoms and the Maternal Mood Screener (MMS) (32) to assess current and lifetime major depressive episode. The MMS is a self-report checklist to assess depressive episodes using DSM-IV criteria that has shown good concordance with diagnostic interviews (33,34). …”
Section: Methodsmentioning
confidence: 99%
“…Participants screened positive for an MDE if they experienced fi ve or more of the nine symptoms (including Symptom 1 or 2) for 2 weeks or more and the symptoms interfered with their life or activities a lot at any point during their lifetime (Past MDE) or in the last 2 weeks (Current MDE). The MDE Screener is validated and reliable in English and Spanish speakers ( Muñoz, McQuaid, González, Dimas, & Rosales, 1999 ;Vázquez, Muñoz, Blanco, & López, 2008 ) and showed good predictive validity for quit rates in participants with past or current major depression ( Muñoz et al, 1997( Muñoz et al, , 2006. Three diagnostic groups were defi ned: (a) No MDE history, never having an MDE; (b) Past MDE, history of MDEs but no Current MDE; and (c) Current MDE, meeting MDE criteria in last 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This tempers the generalizability of these findings, as reports were provided by visitors to a Web site with no live communication with or verification by a professional. Although the MDE screener showed 97% sensitivity and specificity with clinician-administered measures (Vázquez et al, 2008), this same research found a positive predictive value of .646, suggesting a slightly higher tendency to suggest individuals have MDE even if a clinician-administered measure would not find this. Thus, it is possible that our results may have been different had we used clinician-administered measures.…”
Section: Discussionmentioning
confidence: 92%